Academic Writing and Information Literacy Instruction in Digital Environments A Complementary Approach - Mammadova, Tamilla (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book offers an interdisciplinary approach to the teaching of academic writing and information literacy in a new digital dimension, drawing on recent trends towards project-based writing, digital writing and multimodal writing in Education, and synthesising theory with practice to provide a handy toolkit for teachers and researchers. The author combines a practical orientation to teaching academic writing and information literacy with a grounding in current theories of writing instruction in the digitalized era, and argue that as digital environments become more universal in modern society - particularly in the aftermath of the coronavirus pandemic - the lines between traditional academic writing and multi-modal digital writing must necessary become blurred. This book will be of use to teachers and instructors of academic writing and information literacy, particularly within the context of English for Academic Purposes (EAP), as well as students and researchers in Applied Linguistics, Pedagogy and Digital Writing. .
Chapter 1: Introduction -- Chapter 2: Acknowledged Digital Era -- Chapter 3: Writing is a Challenge -- Chapter 4: Pedagogy of Writing and Digital Writing -- Chapter 5: Information Literacy and Digital Literacy -- Chapter 6: Facilitating Collaboration -- Chapter 7: Grading and Feedback -- Chapter 8: Student Academic Support Services. .
Keywords: Applied linguistics; Philology; Literacy; Penmanship; Applied Linguistics; Languages; Literacy; Writing Skills